Individual vs. Team Sport Failure—Similarities, Differences, and Current Developments - Wergin, V. Vanessa; Mallett, Clifford J.; Beckmann, Jürgen (Frontiers in Psychology, 2022)
The construct of “choking under pressure” is concerned with the phenomenon of unexpected, sudden, and significant declines in individual athletes’ performances in important situations and has received empirical attention in the field of sport psychology. Although a number of theories about the reasons for the occurrence of choking under pressure exist and several intervention approaches have been developed, underlying mechanisms of choking are still under debate and the effectiveness of existing interventions remains contested. These sudden performance declines also occur in team sport. “Collective sport team collapse”, which describes the situation when an entire sport team underperforms significantly within an important competitive situation, has received less empirial attention, in comparison to individual choking research. While there are a few studies that have investigated causes of collective team collapse, understandably, there has been limited empirial investigation of preventative and intervention strategies. Although the two constructs appear to share several similar characteristics and mechanisms, research has not yet examined the conceptual, theoretical, empirical, and practical links between choking under pressure and collective sport team collapse. In this review article, we seek to examine these similarities and differences and identify new ways of thinking about future interventions. Furthermore, current empirical understandings in the field of choking under pressure and collective sport team collapse are presented and the most effective intervention approaches for both constructs are introduced. On the basis of this examination, we modestly make some initial recommendations for sport psychological practitioners and future research.